2010
DOI: 10.1089/apc.2009.0309
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy and HIV Transmission Risks: Implications for Test-and-Treat Approaches to HIV Prevention

Abstract: HIV transmission may be prevented by effectively suppressing viral replication with antiretroviral therapy (ART). However, adherence is essential to the success of ART, including for reducing HIV transmission risk behaviors. This study examined the association of nonadherence versus adherence with HIV transmission risks. Men (n ¼ 226) living with HIV=AIDS and receiving ART completed confidential computerized interviews and telephone-based unannounced pill counts for ART adherence monitoring. Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 35 publications
2
56
1
1
Order By: Relevance
“…A study of HIV positive men in receipt of anti-retroviral therapy (Kalichman et al, 2010) reported an association between the belief that an undetectable viral load reduces the chance of HIV transmission and both a greater number of (sero-discordant) sexual partners and condomless sex. What the current study contributes is a greater understanding of the subtle nuances of how risk reduction is managed, how it is highly contextual, how the stories told about sexual practice depends on when and with whom men are speaking, and how perceptions of risk reduction are influenced by perceived social norms and shared notions of morality.…”
Section: Discussionmentioning
confidence: 99%
“…A study of HIV positive men in receipt of anti-retroviral therapy (Kalichman et al, 2010) reported an association between the belief that an undetectable viral load reduces the chance of HIV transmission and both a greater number of (sero-discordant) sexual partners and condomless sex. What the current study contributes is a greater understanding of the subtle nuances of how risk reduction is managed, how it is highly contextual, how the stories told about sexual practice depends on when and with whom men are speaking, and how perceptions of risk reduction are influenced by perceived social norms and shared notions of morality.…”
Section: Discussionmentioning
confidence: 99%
“…Non-adherence has been associated with greater number of sex partners and engaging in unprotected anal intercourse in some but not all studies. 35,36 In addition to the increasing viral load, just under 50% patient had a CD4 count < 200 cells/lL during the TI, placing these patients at increased risk of AIDS-defining illness. The drop in CD4 count and rebound in viral load seen here are consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…This also includes the need to encourage people to have this carried out, considering that models of HIV prevention based on taking the test could increase timely diagnoses and treatment, with beneficial effects in the medium and long term. 38 Other specific recommendations include:…”
Section: Discussionmentioning
confidence: 99%